Contribution of life course cardiovascular risk factors to racial disparities in dementia incidence - Ferguson, Erin L.; Vittinghoff, Eric; Zeki Al Hazzouri, Adina; Allen, Norrina; Fitzpatrick, Annette; Yaffe, Kristine (Frontiers in Dementia, 2023)
Background: Racial disparities in dementia outcomes persist in the United States. Targeting modifiable risk factors, including cardiovascular risk factors (CVRFs), is a conceivable way to reduce health disparities. Life course CVRFs are often higher in non-White adults and are associated with risk of dementia, but it is unknown whether they contribute to racial disparities in dementia and cognition.Methods: Using a pooled cohort of 4,159 White and 939 Black participants aged 65-95 years, we conducted a mediation analysis to estimate the proportional effect of race on dementia that is explained by four CVRFs imputed over the life course (20-49, 50-69, and 70-89 years of age): body mass index, fasting glucose, systolic blood pressure, and low-density lipoprotein cholesterol.Results: Compared to White participants, Black participants had greater risk of dementia (adjusted OR=1.37; 95% CI: 1.17-1.60). BMI and fasting glucose over the life course were significant mediators of the effect of race on dementia risk, mediating 39.1% (95% CI: 10.5-67.8%) and 8.2% 2 (95% CI: 0.1-16.2%) of the effect, adjusted for sex and age. All four CVRFs together were also significant mediators of the effect of race on scores on global cognition and processing speed, accounting for approximately 11% of the effect.We found that CVRFs across the life course partially explain disparities in dementia risk and cognition in late-life. Improved prevention and treatment of CVRFs across the life course may be important to reduce health disparities for dementia.